“Efecto de fungicidas sobre enfermedades fungosas del frejol (phaseolus vulgaris L.), en Aucaloma, Lamas, San Martín” - Tuanama Valera, James Freddy (2015)
The research aimed to evaluate the effect of fungicidas to control fungal diseases in Phaseolus vulgaris L. varied "Huasca Huallaga bean" in Lamas - San Martín. We execute the Fundo Aucaloma, National University of San Martín - T, located in the province Lamas, Department of San Martin; Latitude sur 6 º 20 76 º 21 West Longitude, Altitude 650 m. m. s .n. m, living area bh - T; under complete randomized block randomized with 6 treatments and 4 replications design; the variables evaluated are incidence and severity of foliar diseases and aspects of crop yield. Ali fungicidas applied have reduced the incidence and severity of foliar diseases caused by fungí Psedocercopsorella albida, Rhizoctonia solani, and Phaeroisariopsis griseola: The fungicida benomyl (T5) dose 1 g / I of a shown better results in terms of number of pods per plant (37.4) and yield per hectare (927.83 kg I ha). T4 and T5 treatment that corresponded fungicida Benomyl 1 g I 1 of water and Mancozeb Metalaxyl + 3 g / I of water and 273.32 g 274.65 100 grains of seeds statistically have surpassed ali treatments. Higher profitability was obtained with treatment T5 and T2 representad by the fungicida benomyl at 1 g / I of water and propineb to 3 g / I water and obtained in terms of cost I benefit 13 cents soles and 0.2 cents soles.